Prevalence of Asymptomatic Gallstone during Routine Ultrasonography and its Associated Factors: Cross-Sectional Study from a Tertiary Care Teaching Hospital - Prabha Thangaraj; Vijayashree Jayagopalan; Saraswathi Selvaraju (GAIMS Journal of Medical Sciences)
Background: Gallstones are the most important risk factor for gall bladder carcinoma. Understanding the burden of asymptomatic gallstone and its associated factors is essential to identify risk group likely to develop complication.